A study on remote communication from the idea of precognition - Francisco do Nascimento, Flávio (Circumscribere International Journal for the History of Science, 2022)
In the middle of the twentieth century, precisely during the Cold War, there was a great development in remote communication technologies, such that the empires, Soviet and North American, could watch one another from a distance, ensuring them political-military expansion and safety. That development has been inextricably linked to the theoretical currents, mathematical and systemic, that concurred for the scientific consolidation of information sciences. We suggest that these same currents have been used as possibilities to explain the precognition’s parapsychological mechanism, which concerns the early knowledge of information and that has been object to the debate of the articles we have analyzed. And surrounding this debate, we have presented evidence that the precognition shapes itself as the ideas, and also the implement of information technologies, consolidate themselves as intentional instruments of power and control of social behavior through remote communication.